Encuesta sobre nuevas dinámicas en la forma de gobierno - Aranda Álvarez, Elviro; Carmona Contreras, Ana; García-Escudero Márquez, Piedad; Guillén López, Enrique; Ridao i Martín, Joan; Seijas Villadangos, Esther (Teoría y Realidad Constitucional, 2023)
Encuesta sobre nuevas dinámicas en la forma de gobierno